Inclusive Governance and Wealth Distribution: An Islamic Perspective - Maisuna Maisuna; Alwy Ahmed Mohamed (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Inclusive governance and equitable sustainable wealth distribution is a core challenge in contemporary economic and political leadership around the world, occasioned by exclusionary, restrictive, selective, and discriminatory systems of governance. Unlike what it entails in Western models of governance, Islam has inherently established a system of governance that caters for people’s welfare, advocates accountability, emphasizes equity and justice, and shows concern for neighbours and community members irrespective of status, gender, ethnicity, religion, political, and economic class, etc. The problem, as observed in this paper, is rooted in the method of governance in Nigeria, which is based on undue accumulation and excessively gives power to a few for wealth accumulation. As such, this results in abject poverty within the circle of the middle and lower-middle class of the citizenry. The paper, therefore, adopts historical methodology and sources to assess relevant literature, with particular emphasis on primary sources of Islam. The paper recommends that governance should recognize the dignity, welfare, and economic needs of every member of the society, as Islam recommends inclusivity in its system of governance and circulation of wealth among others. The paper draws the conclusion that the Islamic system of governance encourages inclusivity and circulation of wealth through its proportionate use of sadaqah (charity), zakah (alms), endowment (waqf), inheritance (mirath), etc.